1982
DOI: 10.1111/j.1365-2621.1982.tb07690.x
|View full text |Cite
|
Sign up to set email alerts
|

Maillard Browning Reaction of Sugar‐Glycine Model Systems: Changes in Sugar Concentration, Color and Appearance

Abstract: The reactivities of glucose, fructose, and sucrose with glycine (1:l molar ratio) at 60°C and pH 3.5, were compared over 280 hr. While fructose initially browned at a faster rate, it was overtaken by glucose after 80 hr. Initially more fructose than glucose was consumed, but the reverse was true after 60 hr. Sucrose was readily hydrolyzed under these reaction conditions and underwent MailIard browning reactions, its color and appearance being similar to the glucose solutions at the later stages of the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 4 publications
3
25
0
Order By: Relevance
“…The formation of color in foods during heat processing is contributed to nonenzymatic browning, generated from both MR and caramelization. Caramelization occurs more so at high heating temperature (N 120°C) along with extreme pH (b3 or N9) (Reyes, Poocharoen, & Wrolstad, 1982). Dramatic decreases in E index occurred within 5 min of heating at both 150°C and 180°C temperatures in pentose-amino acid models (Xyl-Gly, Xly-Lys, Rib-Gly, and Rib-Lys) ( Fig.…”
Section: Color Index (E)mentioning
confidence: 96%
“…The formation of color in foods during heat processing is contributed to nonenzymatic browning, generated from both MR and caramelization. Caramelization occurs more so at high heating temperature (N 120°C) along with extreme pH (b3 or N9) (Reyes, Poocharoen, & Wrolstad, 1982). Dramatic decreases in E index occurred within 5 min of heating at both 150°C and 180°C temperatures in pentose-amino acid models (Xyl-Gly, Xly-Lys, Rib-Gly, and Rib-Lys) ( Fig.…”
Section: Color Index (E)mentioning
confidence: 96%
“…This indicated that HMF was formed at a higher rate at elevated temperatures and subsequently this phenomenon affected brown pigment formation. Several works studied the Maillard reaction in aqueous systems containing glucose and amino acid (Carabasa-Giribet & Ibarz-Ribas, 2000;Gogus, Bozkurt, & Eren, 1998;Reyes, Poocharoen, & Wrolstad, 1982). Garza et al (1999) reported that the HMF content increased with treatment time.…”
Section: -Hydroxymethylfurfural (Hmf) Accumulation and Brown Pigmentmentioning
confidence: 98%
“…In the field of food science, it is well-known that MR causes not only a browning of color and flavor change, but also loss of nutritional or functional value. [1][2][3][4] Since this is a serious problem for the shelf life of low-moisture dry food, 5,6) control or prediction of the MR rate is an important subject.…”
mentioning
confidence: 99%